2022
DOI: 10.1186/s13690-022-00904-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of COVID-19 vaccine behaviour intentions among the youth in Kenya: a cross-sectional study

Abstract: Introduction COVID-19 has become a public health concern globally with increased numbers of cases of the disease and deaths reported daily. The key strategy for the prevention of COVID-19 disease is to enhance mass COVID-19 vaccination. However, mass vaccination faces challenges of hesitation to acceptance of the vaccine in the community. The youth may not be among the vulnerable population to severe COVID-19 disease but are highly susceptible to contracting the virus and spreading it. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…However, the association between gender and acceptance of the COVID-19 vaccine was not statistically significant among adults in the current study. However, in our study, COVID-19 vaccine hesitancy was higher among Orthodox Christians (43). According to reports from other settings, religiosity appeared to have an impact on the decision to be inoculated with the vaccine (44,45).…”
Section: Discussioncontrasting
confidence: 63%
“…However, the association between gender and acceptance of the COVID-19 vaccine was not statistically significant among adults in the current study. However, in our study, COVID-19 vaccine hesitancy was higher among Orthodox Christians (43). According to reports from other settings, religiosity appeared to have an impact on the decision to be inoculated with the vaccine (44,45).…”
Section: Discussioncontrasting
confidence: 63%
“…The major impediment to vaccine uptake was perceived vaccine effects and has also been cited in past studies [29] , [23] , [17] , [16], [27], even among health workers [30] [31] In a study among American with disabilities, vaccine effects were similarly glaring with the study highlighting higher concerns about COVID-19 vaccine safety as compared to concerns about contracting the disease. Our study revealed further that most of the purported effects were heard from external sources mainly social contacts.…”
Section: Discussionmentioning
confidence: 98%
“…On the low vaccine uptake among the youth, Osur et al established the main causes of vaccine hesitancy among youth in Kenya to be concerns about vaccine safety and effectiveness, with social media as the major source of information contributing to hesitancy. [17] Higher vaccine hesitancy was also reported in younger persons with intellectual and developmental disabilities in New York state individuals by [18]. Some studies have also reported lower likelihood of vaccine hesitancy among the elderly [19] [20].…”
Section: Discussionmentioning
confidence: 99%
“…According to a report dated 11 October 2022 [ 7 ], this rate is about the same as the rate for HICs and above the world average based on the whole population. Nearly half the people who hesitated to get vaccinated, in the range of 20–40% reported in the literature [ 39 , 40 , 47 , 48 ], accepted the vaccine later. As a dimension of vaccine hesitancy, the presence of individuals who both accept the vaccine and maintain their concerns or postpone vaccination due to their concerns [ 15 ] may be in question in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results from research involving healthcare students in Vietnam linked around 40% of the students to vaccine hesitancy, which was attributed to vaccine manufacturers’ failure to disclose the adverse effects of the products and to some students’ belief that possible side effects may result in death [ 39 ]. In a cross-sectional study investigating COVID-19 vaccine behavioral intentions among youth in Kenya, the vaccine’s perceived adverse effects were among the critical factors causing vaccine hesitancy [ 40 ]. Finally, a study conducted in Nigeria that compared the attitudes toward vaccines of rural and urban young populations revealed that the young rural population was more willing to vaccinate than the young urban population [ 41 ].…”
Section: Introductionmentioning
confidence: 99%